A risk evaluation framework for the best maintenance strategy: The case of a marine salt manufacture firm. (January 2021) - Carpitella, Silvia; Mzougui, Ilyas; Benítez, Julio; Carpitella, Fortunato; Certa, Antonella; Izquierdo, Joaquín; La Cascia, Marco
Highlights: This paper proposes a MCDM framework to support risk evaluation for maintenance activities. The ANP is proposed to select the best maintenance strategy on the basis of real systems' features. The ELECTRE III is used to prioritise the main risks related to the interventions of the selected maintenance policy. The proposed framework is applied to a core subsystem of a real-world marine salt manufacture firm. Abstract: This paper intends to contribute with a multi-criteria decision-making (MCDM) framework to support risk evaluation for maintenance activities carried out on critical systems in industry. We propose to first select the best maintenance strategy tailored to companies' requirements and systems' features, and second to perform a risk prioritisation aimed at highlighting priorities of intervention. The Analytic Network Process (ANP) is suggested to select the maintenance policy representing the best trade-off considering the complex and varied interdependencies amongst a diversity of clustered elements characterising the system. Then, the main risks related to the interventions associated to the selected maintenance policy are ranked using the ELimination Et Choix Traduisant la REalité III (ELECTRE III) method, using the same criteria weighted by the previous ANP application. This hybrid MCDM framework is applied to a core subsystem of a real-world marine salt manufacture firm.